Stalin's Gulag at War : Forced Labour, Mass Death, and Soviet Victory in the Second World War - Bell, Wilson T., 1977- (University of Toronto Press, 2018)
Stalin's Gulag at War places the Gulag within the story of the regional wartime mobilization of Western Siberia during the Second World War. The author explores a diverse array of issues, including mass death, informal practices, and the responses of prisoners and personnel to the war.